Concrete structure, properties, and methods - Mehta, P.K. (Povindar K.) (Prentice-Hall international series in civil engineering and engineering mechanics, 1993)
Covers the art and science of concrete, emphasizing structure-property relations. This new edition gives improved coverage of viscoelastic behaviour and covers treatment of thermal shrinkage and stresses, plastic settlement cracks and crazing, and technology of structural lightweight concrete.